Orang Asli Socio-Development Index Instrument in Malaysia - Zulkipli Syaaibah (EDP Sciences, 2021)
Orang Asli is among the marginalized communities in Malaysia which perceived to have a very low performance in various social indicators. Though of numerous efforts of transformational and development programs initiated by the government, there are no specific measurement tool or instrument to evaluate the performance these initiatives as to verify the effectiveness of government policies. This paper aims to propose an index instrument to assess the socio-development of Orang Asli in Malaysia. The development of this index will employ Fuzzy Delphi Method (FDM) to determine the indicators and sub-indicators of the index, and Analytical Hierarchy Process (AHP) to determine the weightage of each indicators and sub-indicators. The proposed Orang Asli socio-development index is expected to be the base of government strategies and action plan to provide a better living quality to Orang Asli community in Malaysia.